EVALUATION OF STRUCTURAL PERFORMANCE OF INSTALLATION BUILDING AND INPATIENT WARD IN DISTRICT HOSPITAL OF WATES USING SOFTWARE SAP-2000 - atmaka, aswin andre (Universitas Bengkulu, 2020)
This District Hospital of Wates was developed and constructed to meet medical need for local people of Kulon Progo District and this hospital was expected to have impact on the public economy wheel improvement. This hospital has a reinforced concrete structure to support the standing torque with five floors in 4.5-m height of each floor and has 20.5-m height. The building structure must be able to support earthquake force at specific level without significant damage of structure or, if the building must fail. The objective of this study was to find performance point value of the building, ratio drift value based on ATC-40 and performance level. This study evaluated the building performance of the hospital based on spectrum response and national standard of Indonesia. The results of study indicate that Performance Point value with X-direction slide force was 3188.541 kN and Y-direction was 1058.513. On the other hand, ratio drift value, based on ATC-40, had maximum in-elastic drift of X-direction = 0.000000249 and maximum In-elastic drift of Y-direction = 0.000000405, it means that the reviewed building was included in level of Immediate Occupancy (IO) so that the building of hospital, when earthquake faced it, did not experience structural and non-structural damage; therefore, this building remained safe. Keywords : Pushover, Perfomance Point , Ratio Drift, ATC-40